Macroeconomic Fundamentals, Stock Market and Economic Growth - Chong, Lee Lee (2000)
This study investigates the dynamic relationships amongst the KLSE stock prices, macro variables and economic growth. It is a general belief that the macro variables, namely the inflation rate, interest rate, aggregate output, money supply, exchange rate and the trade balance are some prominent factors to the performance of the stock market. The stock market, in tum, is one of the leading indicators for the economic growth. The VAR model of Johansen-Jeselius multivariate cointegration test, multivariate Granger-causality test, and also the impulse response function are applied to capture the dynamic linkages among those variables over the period of 1987:1 to 1997:2. In this study, the Composite Index is used to represent the general performance of the market. The performance of individual sectors, on the other hand, is measured by the individual sectoral indices. These sectoral indices include the Industrial Index, Finance Index, Property Index, Plantation Index and the Mining Index. The empirical results of this study indicate that the stock indices and macroeconomic variables are moving together towards its equilibrium path in the long run. In the short run, there are evidences of contemporaneous causality running between the variables. The results show that the general performance of market, which is reflected by the Composite Index, is caused by the changes in inflation, output, money supply and the trade balance. The sectoral performance, on the other hand, has shown different responses to the fluctuations in the macroeconomic variables. The property sector appears to be the least sensible to these fluctuations. Besides, the physical capital, stock capitalisation and its trading activities are also the important factors that contribute to the economic growth. This study thus implies that an efficient management of macroeconomic policies will promote a better performance of stock market, which in turn helps to achieve a stronger and sustainable economic growth.